BRANDING PEMIMPIN NASIONALIS BASUKI TJAHAYA PURNAMA DALAM DEBAT PILKADA DKI JAKARTA 2017 (Menurut Kode-Kode Televisi John Fiske) - Citra Orwela (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2017)
Basuki Tjahaya Purnamais one of governor candidates for DKI Jakarta 2017. As an incumbent, Ahok (his nickname) has been continued Joko Widodo, which was resigned after won the president election. Ahok had been governor candidate that got highlights in many headline news. This happens because his blunder when he socialized his program in Kepulauan Seribu. He made statement about Al-Qur’an and a part of moslem in Indonesia offended with his statement.One of qonsequences is the destruction of his image as the leader that can embrace the people accros their culture, religion, race and social status. John Fiske Television Codes Model mandated three steps of data analysis on scenes that appear in the Ahok’s debating performance within the last debate in the second season. First, the analysis found a reality construction by Ahok that displaying within speech. Ahok presents himself as populist leader and accepted by the society. A representasion in public debating showed Ahok accepted by ethnic groups and social in Jakarta who positioned to provide a solution to the problem of low and middle class. It displaying within ‘kotak-kotak’. Analysis of the ideology that reached based on reality and representasion by the author shows Ahok foundation of communication in the debate season is to using an emotional approach. This article will analyzeAhok’s perfomancein public debating fo governor election in DKI Jakarta in the second season. The researchers concluded such as accepted social classes, ethnic groups amd nationalism. Of the three ideologies, Ahok focused use nationalist leader as an attempt to construct the brand image of Ahok as a candidate during the Jakarta Governor 2017 in his strategy of political marketing. These results showed that Ahok is a leader who displays himself with nationalist leader.